Evaluation of selenite reduction under salinity and sulfate stress in anaerobic membrane bioreactor - Zhang, Yuanyuan; Liu, Shuang; Zhang, Gaorong; Peng, Yixiang; Wei, Qiaoyan; Jiang, Minmin; Zheng, Junjian (Frontiers in Bioengineering and Biotechnology, 2023)
Current microbial reduction technologies have been proven to be suitable for decontaminating industrial wastewaters containing high concentrations of selenium (Se) oxyanions, however, their application is strictly limited by the elemental Se (Se0) accumulation in the system effluents. In this work, a continuous-flow anaerobic membrane bioreactor (AnMBR) was employed for the first time to treat synthetic wastewater containing 0.2 mM soluble selenite (SeO32−). The SeO32− removal efficiency by the AnMBR was approachable to 100% in most of the time, regardless of the fluctuation in influent salinity and sulfate (SO42−) stress. Se0 particles were always undetectable in the system effluents, owing to their interception by the surface micropores and adhering cake layer of membranes. High salt stress led to the aggravated membrane fouling and diminished content ratio of protein to polysaccharide in the cake layer-contained microbial products. The results of physicochemical characterization suggested that the sludge-attached Se0 particles presented either sphere- or rod-like morphology, hexagonal crystalline structure and were entrapped by the organic capping layer. According to the microbial community analysis, increasing influent salinity led to the diminished population of non-halotolerant Se-reducer (Acinetobacter) and increased abundance of halotolerant sulfate reducing bacteria (Desulfomicrobium). In the absence of Acinetobacter, the efficient SeO32− abatement performance of the system could still be maintained, as a result of the abiotic reaction between SeO32− and S2- generated by Desulfomicrobium, which then gave rise to the production of Se0 and S0.